The association of CGG repeat length and AGG interruption patterns on FMR1 alleles with female infertility - Xuanyou, Zhou; Naixin, Xu; Xianling, Cao; Weihui, Shi; Shuyuan, Li; Songchang, Chen; Chenming, Xu (Frontiers in Endocrinology, 2025)
BackgroundThe aim of the present study was to investigate whether the CGG repeat length and AGG interruption patterns on the FMR1 gene affect female fecundity.MethodsA total of 266 infertile patients and 276 fertile controls were included in the study. All participants received FMR1 testing using triplet repeat primed PCR and capillary electrophoresis. The allele with the smaller number of CGG repeats was defined as "allele 1", and the allele with the larger number of CGG repeats was defined as "allele 2".ResultsThe mean number of CGG repeat length at allele 2 in the secondary infertility group was higher than that in the control group (33.1 ± 6.7 vs 30.9 ± 3.3, Bonferroni corrected p=0.003). The proportion of 35–44 CGG repeat at both FMR1 alleles showed a higher trend in the secondary infertility group as compared to the control group after adjusting for age, education, smoking status, cohort and the CGG repeats of the other FMR1 allele (aOR=7.812, 95% CI 0.884-69.001; p=0.064 for allele 1; aOR=3.657, 95% CI 2.193-6.098; p<0.001 for allele 2, respectively). Lower AMH levels were associated with increased CGG repeat length at allele 1 in infertile patients (Adjusted R2 = 0.178, p=0.003) after adjusting for age, education, smoking status, infertility type and the CGG repeats of FMR1 allele 2. However, no significant correlation was found between the number of CGG repeats at allele 2 and AMH levels (Adjusted R2 = 0.150, p=0.086). Although the difference was not statistically significant, there was a higher proportion of 3 AGG interruptions at both alleles in the secondary infertility group as compared to the control group (6.1% vs 0%, p=0.146 for allele 1, 30.6% vs 11.3%, p=0.099 for allele 2). Patients with 35–44 CGG repeat length showed a higher carrier rate of 3 AGG interruptions at both alleles (p<0.001 for both).ConclusionsOverall, the high normal sized (35–44 CGG) repeat length at both FMR1 alleles may serve a promoting role in the development of secondary infertility in Asian women. In addition, the CGG repeat length at allele 1 appears to have a mild correlation with AMH levels in infertile patients.